A comparative evaluation of wear resistance of three types of artificial acrylic teeth after removing the glaze layer - Samaneh Abbasi; Saeed Nikanjam; Arash Shishehian; Sara Khazaei; Farnoush Fotovat; Nilofar Heydar Pana (Wolters Kluwer Medknow Publications, 2022)
Background: The posterior denture teeth wear faster than the anterior teeth, which can result in occlusal interferences, loss of vertical dimension of occlusion, greater stress accumulation in the anterior region, and higher ridge resorption. This study aimed to compare the wear resistance of three types of artificial acrylic teeth before and after removing the glaze layer. Materials and Methods: This in vitro study compared three types of artificial acrylic teeth, namely, Finex (F), SR Orthotyp DCL (S), and Vita Physiodents (V) in six groups (n = 10). Half of the artificial teeth of each brand underwent 0.5-mm buccal reduction to remove the glaze layer (groups FC, SC, and VC). The teeth were thermocycled and placed in a chewing simulator. The teeth with and without the glaze layer were weighed before and after the wear test. The data were analyzed using ANCOVA (the level of significance was 0.05). Results: The weight reduction (indicative of wear) was 0.03 ± 0.02 and 0.12 ± 0.03 mg in Groups S and SC, 0.03 ± 0.02 and 0.25 ± 0.04 mg in Groups V and VC, and 0.11 ± 0.15 and 0.28 ± 0.1 mg in groups F and FC, respectively. Removing the glaze layer (P < 0.01), type and brand of acrylic tooth (P < 0.01), and the baseline weight of artificial teeth (P < 0.01) had significant effects on wear resistance of artificial teeth. Conclusion: The wear of artificial teeth was greater after removing the glaze layer, and the magnitude of wear was also significantly different among the three brands. The group FC showed maximum wear while the groups S and V showed minimum wear.